The Influence of Sales Promotion and Product Quality on Consumer Purchasing Decisions - Adinugroho, Iwan (Jurnal Informatika Ekonomi Bisnis, 2025)
The rapid growth of the culinary small and medium enterprise (SME) sector has intensified business competition, requiring firms to implement effective marketing strategies to influence consumer purchasing decisions. This study aims to analyze the effect of sales promotion and product quality on consumer purchasing decisions at the Mie Wong Solo Home Industry SME in Mamuju Regency, West Sulawesi. The research employs a quantitative approach using a descriptive verificative design. Primary data were collected through questionnaires distributed to 30 consumers selected using purposive sampling. The data were analyzed using multiple linear regression supported by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results show that sales promotion and product quality simultaneously have a positive and significant effect on consumer purchasing decisions. Partially, sales promotion has a significant influence on purchasing decisions, while product quality shows a stronger and more dominant effect. The coefficient of determination indicates that more than half of the variation in purchasing decisions can be explained by the combined influence of both variables. These findings imply that SMEs must integrate effective promotional strategies with consistent product quality improvement to strengthen competitiveness and sustain long-term customer loyalty. This study also provides practical insights for SME managers in designing balanced and sustainable marketing strategies.